Occupancy implications on Indoor Air Quality (IAQ) in selected primary school classrooms around Kuantan, Pahang - A. H., Hazrin; Z., Maryam; A., Hizrri; Norhidayah, Abdull; Niza, Samsuddin; M. A., Mohd Shukri (Malaysian Public Health Physicians Association, 2017)
The effects of children’s exposure on high concentration of airborne pollutants at schools often associated with increased rate of absenteeism, low productivities and learning performances, and development of respiratory problems. Recent studies have found that the presence of occupants in the classroom seems to give major effect towards the elevation of concentration of airborne pollutants in indoors. In order to evaluate and further understand on the significance of occupancy factor on IAQ, this study has been designed to determine and compare the level of selected physical (particulate matter (PM)) and chemical (carbon dioxide (CO2) and temperature) IAQ parameters and biological contaminants via colony forming unit (CFUm-3 ) for bacteria and fungi inside the selected classrooms during occupied and non-occupied period (first objective). The second objective is to describe the possible sources of airborne pollutants inside the classrooms at the selected primary schools around Kuantan, Pahang. Assessments of physical and chemical IAQ were done by using instruments known as DustMate Environmental Dust Detector and VelociCalc® MultiFunction Ventilation Meter 9565.The data were recorded every 30 minutes for 8 hours during schooldays and weekend at the selected sampling point in the classrooms. For microbial sampling, Surface Air System Indoor Air Quality (SAS IAQ) was used to capture the bacteria and fungi. The data obtained were compared with the established standard reference known as the Industrial Code of Practice on Indoor Air Quality (2010) constructed by the Department of Occupational Safety and Health (DOSH), Malaysia. This study has found that some of the IAQ parameters in the selected classrooms were exceeding the established standards during occupied period in schooldays compared to non-occupied period during weekend. Findings of this study provide the insights for future research including the site selection of school, arrangement of the classrooms and numbers of students per class.